“Por que Fanon? Por que agora?”: Frantz Fanon e os fanonismos no Brasil - Faustino, Deivison Mendes (2015)
This paper discusses the different ways, uses and appropriations of the thought of Frantz Fanon in Brazil between the 1950s and the present day. The study approaches Wynter (1999) and Gordon (2015) to identify the perspective of sociogenesis the structural axis of fanoniano theoretical status, and Hall (1996) and Sekyi-Otu (1996) to recognize the author's thought the open joint and not completed theoretical and various political elements. From this evidence, it argues that the legacy of Fanon is claimed differently by different theoretical aspects, and sometimes conflicting. In Brazil, the reception of Fanon occurred under the influence of the third Worldism revolutionary and its focus on Les Damnés de la terre. Providing both the players connected to the left as readers more attuned to the black movement, a guided appropriation the polarization between colonizer and colonized and affirmation of identity (national or black) as opposed to colonization. But the contemporary period, marked by a growing interest in the reflections of Fanon, is structured by a greater diversity of approaches and theoretical focus, setting six sub-fields: 1.Estudos Postcolonial and the Diaspora; 2. Negritude; 3. Decolonial; 4. Whiteness; 5. Psychology; 6. National Ethos.